Lontar Roga Sanghara Bhumi: Ritual Referention for Natural Balancing in Bali - Jirnaya, I Ketut (International Research Journal of Management, IT & Social Sciences, 2016)
Lontar Roga Sanghara Bhumi was a script about natural disasters that occurred in the world, natural disaster signs, natural phenomenon unlike good and bad signs, as well the forecast towards earthquake impact based on sasih (month of Bali) the earthquake occurrence. The signs were analyzed of eco-semiotic and meaning was knowable behind it. Balinese society trust that peace and harmony in life happened if it was occurred Tri Hita Karana (there was a balance correlated between human and God, human and fellow human beings, and human beings with bhutakala/Balinese term of evil). Conversely, natural disasters was occurred due to human activity that has soiled the world so that the Gods was angry. The bhutakala was instructed to make a disaster by the Gods. In order to anticipate and naturalize natural disasters occurrence, Balinese society regularly performed rituals of salvation as a means of communication apologize to God. The ritual has its level i.e. prayascita, guru piduka, labuh gentuh.